Aplikasi Alat Tanam Padi Sistem Jarwo di Desa Batunyala Kecamatan Praya Tengah Lombok Tengah - Sujita Sujita; Nasmi Herlina Sari; Sinarep Sinarep; Achmad Zainuri; Rudy Sutanto (Jurusan Teknik Mesin FT Universitas Mataram, 2023)
Batunyala Village, Praya Tengah District, Central Lombok Regency is known as a rice barn area in Central Lombok Regency. In general, their livelihood is rice farming. The characteristics of rice from Batunyala Village are fluffier and fragrant with fragrant pandan wangi. So many local and foreign rice traders are looking for it to be sold again. The obstacle experienced by farmers is when planting rice. Planting is an important activity in rice cultivation which requires about 25% of labor. Most of the agricultural workforce is now entering the non-productive age, while the interest of the younger generation to get involved in agriculture is getting lower, especially with traditional farming systems. This situation has raised deep concern for the government in achieving reliable food security. One way to overcome these obstacles is by counseling, as well as applying the rice transplanter (Rice Transplanter) of the Jajar Legowo (Jarwo) Planting Method. The application of Rice Transplanter technology with the Jarwo method can increase time and cost efficiency. The production of Pandan Wangi variety rice produces an average of 4.0 tons/ha and manually produces an average of 3.64 tons/ha. Can increase production by 9.89% compared to the manual system.